2007
DOI: 10.1016/j.febslet.2007.06.065
|View full text |Cite
|
Sign up to set email alerts
|

The CER3 wax biosynthetic gene from Arabidopsis thaliana is allelic to WAX2/YRE/FLP1

Abstract: The cuticle coats the aerial organs of land plants and is composed of a cutin matrix embedded and overlayed with waxes. The Arabidopsis CER3 gene is important for cuticular wax biosynthesis and was reported to correspond to At5g02310 encoding an E3 ubiquitin ligase. Here, we demonstrate that CER3 is not At5g02310 and instead corresponds to WAX2/ YRE/FLP1 (At5g57800), a gene of unknown function required for wax biosynthesis. CER3 protein has also been implicated in cutin production because strong cer3 alleles d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
124
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 41 publications
4
124
0
Order By: Relevance
“…In agreement with this observation, bacteria transformed with a MS2 cDNA produce fatty alcohols from uncharacterized precursors (Doan et al, 2009). A loss-of-function mutation in the FACELESS POLLEN1/YORE-YORE/WAX2 gene that impacts exine structure and wax synthesis (Ariizumi et al, 2003;Chen et al, 2003;Kurata et al, 2003) was reported recently to be allelic to CER3, a gene previously described to fulfill an unknown function in wax synthesis (Rowland et al, 2007). DIHYDROFLA-VONOL 4-REDUCTASE-LIKE1 (DRL1), another gene required for pollen development and male fertility (Tang et al, 2009), shares sequence similarity with DIHYDROFLAVONOL REDUCTASE (DFR), a gene implicated in the biosynthesis of anthocyanins and proanthocyanidins (Shirley et al, 1992), but the DRL1 enzyme is also of unknown biochemical function.…”
Section: Introductionmentioning
confidence: 59%
“…In agreement with this observation, bacteria transformed with a MS2 cDNA produce fatty alcohols from uncharacterized precursors (Doan et al, 2009). A loss-of-function mutation in the FACELESS POLLEN1/YORE-YORE/WAX2 gene that impacts exine structure and wax synthesis (Ariizumi et al, 2003;Chen et al, 2003;Kurata et al, 2003) was reported recently to be allelic to CER3, a gene previously described to fulfill an unknown function in wax synthesis (Rowland et al, 2007). DIHYDROFLA-VONOL 4-REDUCTASE-LIKE1 (DRL1), another gene required for pollen development and male fertility (Tang et al, 2009), shares sequence similarity with DIHYDROFLAVONOL REDUCTASE (DFR), a gene implicated in the biosynthesis of anthocyanins and proanthocyanidins (Shirley et al, 1992), but the DRL1 enzyme is also of unknown biochemical function.…”
Section: Introductionmentioning
confidence: 59%
“…Wild-type control values were arbitrarily set to one. Results are presented as the median 6 95% confidence When grown in soil, stems of the pecp1-3 T-DNA insertional line revealed a "glossy" phenotype that cosegregated with the pecp1 mutation, reminiscent of waxdeficient mutants (Rowland et al, 2007). The second allele (pecp1-1) did not display any such phenotype, suggesting that this phenotype was unrelated to PECP1.…”
Section: Ppspase1 and Pecp1 Are Dynamic Markers Of Pi Starvationmentioning
confidence: 99%
“…Expression of MS2 in Escherichia coli results in the production of alcohols from endogenous E. coli fatty acids (Doan et al, 2009), supporting a function in fatty acid metabolism. Loss of function of the FACELESS POLLEN1/ WAX2/YRE/CER3 gene results in defects in both exine and epicuticular wax deposition, and the gene encodes a putative enzyme of unknown function presumably involved in both wax biosynthesis and pollen wall formation (Ariizumi et al, 2003;Chen et al, 2003;Rowland et al, 2007).…”
Section: Introductionmentioning
confidence: 99%